2001
DOI: 10.1002/app.1277
|View full text |Cite
|
Sign up to set email alerts
|

Study of mechanical and rheological behaviors of linear and branched polycarbonates blends

Abstract: A study of the mechanical and rheological properties of linear and branched polycarbonates blends is presented. Phase separations of the blends were checked through DSC and SEM, and, subsequently, mechanical and rheological properties were investigated. Phase separations were not observed in the blends. The mechanical properties were examined through tensile, flexural, and impact tests. All the mechanical properties of the blends were relatively independent of the compositions. For study of the rheological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…The glass transition temperature of the low molecular weight linear prepolymer (PRE‐0) is 132.8°C but the T g increases with reaction time as both the polymer molecular weight and the insoluble fraction increase. After 180 min of reaction time (SSPM‐180), T g becomes constant at around 159°C which is higher than the reported T g values of commercial linear BPAPC (e.g., 146°C (31,000 g mol −1 ), 153°C (43,000 g mol −1 )) . The presence of partially crosslinked polymer chains copresent with linear BPAPC chains is believed to increase the T g because they would hinder the rotation of chain segments.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…The glass transition temperature of the low molecular weight linear prepolymer (PRE‐0) is 132.8°C but the T g increases with reaction time as both the polymer molecular weight and the insoluble fraction increase. After 180 min of reaction time (SSPM‐180), T g becomes constant at around 159°C which is higher than the reported T g values of commercial linear BPAPC (e.g., 146°C (31,000 g mol −1 ), 153°C (43,000 g mol −1 )) . The presence of partially crosslinked polymer chains copresent with linear BPAPC chains is believed to increase the T g because they would hinder the rotation of chain segments.…”
Section: Resultsmentioning
confidence: 82%
“…It has been reported that molecular weight, molecular structure, and polymer relaxation rate affect the degree of shear thinning . Decreased polymer chain relaxation or diffusion rate for high molecular weight nonlinear polycarbonates with branching and partial crosslinking give rise to higher shear thinning effect . Linear viscoelastic behaviors were observed for the SSPM‐180 and SSPM‐420 which contain about 5 and 49% insoluble gel, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations